UPAYA PENCEGAHAN PENULARAN TB PARU OLEH PASIEN TB KEPADA KELUARGA DI WILAYAH KERJA PUSKESMAS MULYOREJO KOTA MALANG - Arif Dwi Sulistiyanto; Tri Nataliswati; Arief Bachtiar (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Combating Tuberculosis case has become the world's attention and Indonesia become the fifth country with the highest TB burden in the world. Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis that can be transmitted when active lung TB patient coughs, sneezes, or speaks. So inadequate effort to prevent TB infection can increase the risk of transmitted this bacterium to families and increase the incidence of TB. This study aimed to determine the effort to prevent TB transmission of patients with active pulmonary TB to family in working area of Puskesmas Mulyorejo, Malang City. This study design was descriptive and 45 respondents (34.60 + 7.55 years old) were included in this study using total sampling. This study used closed questionnaire as instrument. The result of this studies showedthat effort to prevent transmission of TB of patients with active pulmonary TB to families was 55.5% categories enough. The effort of patients with active pulmonary TB that oftendo is open the window in the morning for better ventilation. This study concludes that patients with active pulmonary TB have sufficient effort to prevent transmission of TB to families.We suggest the effort to prevent transmission of TB can be increased and the effort of health center like PuskesmasMulyorejo should be maintained so that combating of TB can be accomplished.